Endoscopic Endonasal Management of Pterygopalatine Fossa Tumors. Issue 5 (July 2021) - Ozawa, Hiroyuki; Sekimizu, Mariko; Saito, Shin; Nakamura, Shintaro; Mikoshiba, Takuya; Toda, Masahiro; Ogawa, Kaoru
Abstract : Abstract: Surgical removal of pterygopalatine fossa (PPF) tumors with endoscopic endonasal approach is still challenging. The present study aimed to evaluate our endoscopic endonasal management of PPF tumors based on the tumor pathology and purpose of the surgery. This comprised both a single nostril approach for biopsy and a binostril approach for complete resection of benign and noninfiltrating tumors. Based on this strategy, 12 patients underwent endoscopic endonasal surgery for PPF tumors between 2013 and 2018. The patients' data were analyzed retrospectively to demonstrate the significance of our treatment scheme. The surgery was terminated only after taking a biopsy specimen in 6 patients. Other 6 patients underwent gross total resection or bulk tumor reduction. Final pathological diagnosis was malignant in 6 cases and benign in the remaining 6. Post-operative treatment was needed in 7 patients. Four operations for the 6 patients who underwent either debulking or radical surgery were performed by the binostril approach; while 5 surgeries for the 6 biopsy patients were performed by the single nostril approach. Postoperative complications were tolerable. Endoscopic resection should be adopted preferentially for benign tumors that can be removed in a piecemeal fashion. However, as most malignant tumors were impossible to resect with a negative margin, priority should be given to tumor biopsy using an endoscopic approach, which is less invasive than an open approach, and an appropriate treatment customized to the pathological diagnosis should be administered. Abstract : Supplemental Digital Content is available in the text